Efektivitas Mikronutrien Zinc dari Ekstrak Labu Kuning (Cucurbita Moschata D) Terhadap Perilaku Kawin Mencit (Mus musculus) Jantan - Linda Prasetyaning; Risa Purnamasari; Nova Lusiana (Biotropic : The Journal of Tropical Biology, 2018)
Male reproductive ability ability has a linear correlation with libido and testosterone. Both are associated with various things main food consumption such as protein, vitamins and minerals. Aphrodisiac is an ingredient or drug that arouses sexual arousal or libido. Pumpkin is an example of food from plants with the highest content of zinc. This study was to determine whether there is a difference between the content of zinc on the peel, flesh and pumpkin seeds against sexual activity of mice. The experimental animals used were 24 male, group I mice as control group, Group II was grouped with pumpkin peel extract, Group III was grouped with extract of pumpkin flesh, Group IV was grouped with extract of pumpkin seeds. The dose used is 2gr / kg BB and volume of 0.2 ml is given for 35 days. Sexual Activity is observed every day by the position of male mice riding females. Based on Anova One Way test results showed there are differences in sexual activity mice males in each group (ρ 0.000). The difference of the result of the number of mounts indicated that the giving of yellow pumpkin extract had an effect on the increase of mating behavior of male mice. The group treated with the extract of pumpkin flesh showed the highest number of mice mounts (mean = 24,1667.Further research is needed to get a clearer picture of the composition of the pumpkin nutrients that indirectly affect fertility in men.